2020
DOI: 10.1037/qup0000113
|View full text |Cite
|
Sign up to set email alerts
|

“What is it going to be like?”: A phenomenological investigation of racial, gendered, and sexual microaggressions among highly educated individuals.

Abstract: Seven ethnically and racially diverse researchers conducted phenomenological research using a semistructured interview investigating the presence and nature of microaggressions in the lives of 59 highly educated racial, gender, and sexual minority research participants, ranging in age from mid20s to mid60s. The minimum educational requirement for the study participation was a completed master's degree. Participants could be enrolled in a doctoral program and pursuing any discipline or could have previously obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
(45 reference statements)
1
19
0
Order By: Relevance
“…Daily experiences encountering, withstanding, tolerating, and enduring racial microaggressions have psychological and physical costs on targets. Findings from both qualitative and quantitative studies strongly suggest that racial microaggressions are linked to psychological sequelae such as low self-esteem (e.g., Thai et al, 2017), stress (e.g., Hall & Fields, 2015;Torres et al, 2010;Torres & Taknint, 2015), anxiety (e.g., Cheah et al, 2020;Hope et al, 2018;Ramirez & Paz Galupo, 2019;Smith et al, 2007; M. T. Williams, Kanter, & Ching, 2018), depressive symptoms (e.g., Gattis & Larson, 2017;Robinson-Wood et al, 2020;Torres et al, 2010), and suicidal ideation (Hollingsworth et al, 2017;O'Keefe et al, 2015). Research also has provided evidence for the link between racial microaggressions and physiological effects (e.g., Hall & Fields, 2015;Huynh, 2012;Ong et al, 2017).…”
Section: Documenting the Harmful Effects Of Racial Microaggressionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Daily experiences encountering, withstanding, tolerating, and enduring racial microaggressions have psychological and physical costs on targets. Findings from both qualitative and quantitative studies strongly suggest that racial microaggressions are linked to psychological sequelae such as low self-esteem (e.g., Thai et al, 2017), stress (e.g., Hall & Fields, 2015;Torres et al, 2010;Torres & Taknint, 2015), anxiety (e.g., Cheah et al, 2020;Hope et al, 2018;Ramirez & Paz Galupo, 2019;Smith et al, 2007; M. T. Williams, Kanter, & Ching, 2018), depressive symptoms (e.g., Gattis & Larson, 2017;Robinson-Wood et al, 2020;Torres et al, 2010), and suicidal ideation (Hollingsworth et al, 2017;O'Keefe et al, 2015). Research also has provided evidence for the link between racial microaggressions and physiological effects (e.g., Hall & Fields, 2015;Huynh, 2012;Ong et al, 2017).…”
Section: Documenting the Harmful Effects Of Racial Microaggressionsmentioning
confidence: 99%
“…F. Anderson & Finch, 2017; Lewis et al, 2017; Nicholson & Mei, 2020), and various somatic symptoms (J. Y. J. Kim et al, 2019; Nadal et al, 2017; Robinson-Wood et al, 2020). Focusing on Black adults in a qualitative study, Hall and Fields (2015) observed a range of adverse physical health effects (e.g., insomnia and hypertension) that participants attributed to their experiences with racial microaggressions.…”
Section: Documenting the Harmful Effects Of Racial Microaggressionsmentioning
confidence: 99%
“…The macrosystem influences the nature of interaction within all other levels of the ecology of human development" (xiv). As a result, participants recognized subtle and blatant racist interactions with UW White peers, faculty and administrators (Brown, 2018;Hollingsworth, Patton, Allen & Johnson, 2018;Kelly, 2018;Nadal et al, 2014;Robinson-Wood et al, 2015) as purposeful, while also being mindful of institutional racism occurring in K-12 school where zero-tolerance policies disproportionally compromised Black student learning throughout the city were UW was located. Participants constructed themselves as members of the African Diaspora and understood racism as a perpetual occurrence, which validates Bronfenbrenner's (1994) chronosystem as "change or consistency over time not only in the characteristics of the person but also of the environment in which that person lives," (p. 40) to include the belief that Black people live in the afterlife of surviving the transatlantic Slave trade (Hartman, 2007;Womack, 2017).…”
Section: Social Justice As Informed By Informed By Macro-and Chronosymentioning
confidence: 99%
“…Gusa (2010) stated "WIP is the institutionalized fusion of White worldview, White supremacy, and White privilege, and the manifestation of WIP can be categorized into four intricately linked attributes: White ascendancy, monoculturalism, White blindness, and White estrangement" (p. 472). Cumulatively, these attributes manifest holistically as deleterious to Black students whether in the form of subdued racial microaggressions (Harris et al, 2015;Hollingsworth et al, 2018;Nadal et al, 2014;Robinson-Wood et al, 2015;Sue, 2010) or as flagrant racism (Brown, 2018;Kelly, 2018;Smith et al, 2007)-both having a lasting impact degree attainment.…”
Section: Introductionmentioning
confidence: 99%
“…Parents-in-law, in an attempt to become closer to their child-in-law and solidify their relationship with their child, may not be aware of their own communications and behaviors which may be a reiteration of what their child-in-law is experiencing in broader society. For parents-in-law who are struggling in their relationship with a son-or daughter-in-law who is different from them, one approach is to educate them about the negative societal narratives around people of color-such as, Asians or Blacks, among others (Robinson-Wood et al, 2018)to which they might be susceptible. Furthermore, encouraging more inter-generational communication geared towards learning about each others' family experiences and cultures of origin may also promote greater understanding and acceptance.…”
Section: Implications For Social Work Practicementioning
confidence: 99%